Inverse problem of spectral analysis of conflict dynamical systems - Kharchenko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For conflict dynamical systems, we study the problem of the existence and description of initial measures that converge to measures with given spectral distributions.